Hubungan Motivasi Guru Dengan Minat Baca Siswa - nuke febriana (utile: Jurnal Kependidikan, 2019)
Abstract: This study aims to measure how much the motivation of teachers relates to students' interest in reading at SMP Negeri 12 Kota Sukabumi. The method used in this study is a quantitative method. The subjects of this study were class VII students, amounting to 30 students. Sampling in this study uses purposive sampling technique. Data collection techniques are carried out by observation, interview and questionnaire techniques. After processing the data, it is known that there is a relationship between teacher motivation and reading interest of students in Sukabumi City Junior High School 12 by 76% as evidenced by obtaining a correlation number of 0, 97 and t test value obtained that t count> t table is 21.11> 2.05 , with a significant level of 0.05. In addition, because in this study the results of tcounts were greater than t table, the alternative hypothesis (Ha) proposed was accepted and Ho was rejected. So that from this whole study it can be concluded that there is a significant relationship between the motivation of the teacher and reading interest of class VII-C SMP Negeri 12 Kota Sukabumi. Keywords: teacher motivation, student interest in reading